(untitled) (Biological Sciences - PJSIR, 2021)
In present study, pasting properties of wheat varieties were investigated through rapid visco analyzer (RVA). Starch content was determined by Megazyme kit method varied from 68.88 to 72.73%. Pasting properties indicated variability from 65.25 to 67.80 °C (pasting temperature), 3.22 to 6.00 min (peak time), 1330 to 1784 cP (peak viscosity), 645 to 1002 cP (trough viscosity), 1799 to 2565 cP (final viscosity) 685 to 782 cP (breakdown viscosity) and 1154 to 1563 (setback viscosity). Starch content and seven parameters observed from RVA profiles of various wheat varieties were evaluated for their inter- dependence. Starch content indicated a significantly positive association with trough viscosity (r = 0.926*) and final viscosity (r = 0.917*). Present data show that peak viscosity had significant and positive relationship with setback (r = 0.879*) and trough viscosity (r = 0.976**). Novelty statement. Pasting properties determine end use quality of wheat flour and primarily relates to starch content of wheat flour, which is present in largest proportion. In Pakistan, various wheat cultivars are grown in different climate. As a result, the variations in physico-chemical as well as rheological properties of wheat varieties is anticipated. Significant correlations found out in present study are valuable for the evaluation of effect of pasting properties alone and their interaction.